Epitaxial growth of ZnO on GaN/sapphire substrate by radio-frequency magnetron sputtering - 杨晓丽 陈诺夫 尹志刚 张兴旺 李扬 游经碧 汪宇 董静静 崔敏 高云 黄添懋 陈晓峰 王彦硕 (Journal of semiconductors, 2010)
Zinc oxide（ZnO） thin films were grown on n-GaN/sapphire substrates by radio-frequency（RF） magnetron sputtering.The films were grown at substrate temperatures ranging from 400 to 700℃for 1 h at a RF power of 80 W in pure Ar gas ambient.The effect of the substrate temperature on the structural and optical properties of these films was investigated by X-ray diffraction（XRD）,atomic force microscopy（AFM） and photoluminescence（PL） spectra. XRD results indicated that ZnO films exhibited wurtzite symmetry and c-axis orientation when grown epitaxially on n-GaN/sapphire.The best crystalline quality of the ZnO film is obtained at a growth temperature of 600℃.AFM results indicate that the growth mode and degree of epitaxy strongly depend on the substrate temperature.In PL measurement, the intensity of ultraviolet emission increased initially with the rise of the substrate temperature,and then decreased with the temperature.The highest UV intensity is obtained for the film grown at 600℃with best crystallization.